Digitizing Human Sciences to Determine the Individual’s Personality based on Facial Emotions Recognition - Slimani, K; Bourekkadi, S.; Khoulji, S.; Omari, Otmane; Chouya, S.; Kerkeb, M. L. (Transactions on Engineering and Computing Sciences, 2017)
Informatics is a science that develops and opens up to a group of other sciences. The current researches have been established for multiple partnerships between informatics and the rest of the sciences. This is noticed in the integration of Informatics for instance within medicine, economics, and humanities. Researchers have made computer’s software that help draw the emotional state of the individual from the analysis of the movements that appear on the face. Today, we will follow the same plan, but we will not only study facial features. We will determine the personality based on other data and also face dimensions. We will rely on determining the type of personality based on the analysis of specific parts of the face such as the upper part of the front face, the middle section of the nose and the mouth, and the lower jaw section. In the current study, we used a modern scientific methodology that is manifested in the digitization of human sciences and in the analysis of the image by adopting a software product based on determining the dimensions of the face, specifically mathematical and descriptive, and then extracting the conclusions contained in the black box of the software’s information. Our conclusions and results are confirmed by a group of people whom we have adopted in our experiences. Moreover, we did not only define personality but we have also made it possible for individuals to deal with four types. We dealt with many people, but we can recognize the features of their characters only after the experience and keeping in company with them for a long time. There may also be other ways through which we can take a preliminary idea of the person’s character when we deal with the features of the face.